Plumage colour in Padovana chicken breed: growth performance and carcass quality. Issue 3 (3rd July 2018) - Rizzi, Chiara
Abstract: Padovana female chickens of two plumage varieties, chamois (PC) and silver (PS) and their cross (PC male × PS female) were reared from 1 d until 200 d of age, when they were slaughtered. PC has light brown feathers with white edge (chamois), PS has white feathers with black edge (silver); PCxPS has silver plumage (cross-S) or completely white plumage (cross-W) at a ratio, at hatching, of 1:2 as cross-S:cross-W. The chickens were kept in a breeder house from May until December. In a population of Padovana chickens, it seems to be a relationship between the colour plumage and body weight until the sexual maturity: from 2 weeks until 6 weeks of age the PC females exhibited a higher daily growth ( p < .001) than PS, as well as body weight ( p < .01) at 28 weeks. At 200 d, PC showed higher carcase ( p < .05) and thigh ( p < .05) weight than PS, but similar ready-to-cook carcase conformation and pH, colour, water losses and shear force of breast muscle; no difference was checked between the other groups. Under the environmental conditions of the trial, heterosis had a positive effect ( p < .05) on the daily growth until 70 d of age for cross-S. The results shows a sexual dimorphism for body dimensions increasing until the pubertal age for all the groups; therefore, the females should be slaughtered about 8 weeks later than the males for achieving similar body weight and slaughtering performance and carcase quality.